Elasticsearch server : leverage Elasticsearch to create a robust, fast and flexible search solution with ease - Kuć, Rafał; Rogoziński, Marek (Community experience distilled., 2016)
Leverage Elasticsearch to create a robust, fast, and flexible search solution with easeAbout This Book Boost the searching capabilities of your system through synonyms, multilingual data handling, nested objects and parent-child documents Deep dive into the world of data aggregation and data analysis with ElasticSearch Explore a wide range of ElasticSearch modules that define the behavior of a clusterWho This Book Is For If you are a competent developer and want to learn about the great and exciting world of ElasticSearch, then this book is for you. No prior knowledge of Java or Apache Lucene is needed. What You Will Learn Configure, create, and retrieve data from your indices Use an ElasticSearch query DSL to create a wide range of queries Discover the highlighting and geographical search features offered by ElasticSearch Find out how to index data that is not flat or data that has a relationship Exploit a prospective search to search for queries not documents Use the aggregations framework to get more from your data and improve your client's search experience Monitor your cluster state and health using the ElasticSearch API as well as third-party monitoring solutions Discover how to properly set up ElasticSearch for various use casesIn Detail ElasticSearch is a very fast and scalable open source search engine, designed with distribution and cloud in mind, complete with all the goodies that Apache Lucene has to offer. ElasticSearch's schema-free architecture allows developers to index and search unstructured content, making it perfectly suited for both small projects and large big data warehouses, even those with petabytes of unstructured data. This book will guide you through the world of the most commonly used ElasticSearch server functionalities. You'll start off by getting an understanding of the basics of ElasticSearch and its data indexing functionality. Next, you will see the querying capabilities of ElasticSearch, followed by a through explanation of scoring and search relevance. After this, you will explore the aggregation and data analysis capabilities of ElasticSearch and will learn how cluster administration and scaling can be used to boost your application performance. You'll find out how to use the friendly REST APIs and how to tune ElasticSearch to make the most of it. By the end of this book, you will have be able to create amazing search solutions as per your project's specifications. Style and approach This step-by-step guide is full of screenshots and real-world examples to take you on a journey through the wonderful world of full text search provided by ElasticSearch.